GENDER ASPECTS OF THE MANAGEMENT ACTIVITY ORGANIZATION - I. Gvozdkova (Вестник университета)
The article considers the variants of management activities organization based on the gender-specific behavior, thinking and decision-making. The results of scientific studies of gender-specific styles of behavior and management in society and their defining hereditary and non-hereditary factors are analyzed. The research results of the gender features of people distribution by types of managers are presented. The recommendations for the management problems analysis taking into account the different woman and man gender types are given.